Semantische Differenzen Zwischen dänischen und deutschen Tautonymen Personenbezeichnungen - Rajnik, Eugeniusz (Folia Scandinavica Posnaniensia, 2007)
The purpose of the article is to show certain structural (morphological), and in more detail, certain semantic differences between the tautonymic (identical or nearly identical in form) personal nouns (=PB) in Danish and German, that can lead to linguistic errors. The study was based on a representative selection of examples.